A copolymerized polycarbonate resin, preparation method and application thereof
By performing the melt-transesterification polycondensation process of specific dihydroxy compounds and carbonate diester compounds in the polycarbonate resin, a copolymerized polycarbonate resin with high refractive index, high glass transition temperature and high weight average molecular weight was prepared, which solved the problem that the prior art could not meet the application requirements of high-precision optical instruments, and achieved efficient processing of the material and excellent optical properties.
Patent Information
- Application Number
- CN202410061433.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-16
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-01-16
AI Technical Summary
The prior art is difficult to provide polycarbonate resins with high refractive index, high glass transition temperature and high weight average molecular weight, and cannot meet the application requirements for imaging lenses in high-precision optical instruments.
By performing a melt-transesterification polycondensation process of specific dihydroxy compounds with carbonate diester compounds, a copolymerized polycarbonate resin is prepared, and the structural unit ratio is optimized to achieve a comprehensive increase in high refractive index, glass transition temperature and weight average molecular weight.
The high refractive index (1.660-1.930), high glass transition temperature (145-210℃) and high weight average molecular weight (20000-100000) of polycarbonate resin are achieved, making the material easier to process and mold, and is suitable for imaging lenses of high-precision optical instruments.
Smart Images

Figure QLYQS_1 
Figure QLYQS_2 
Figure QLYQS_3
Abstract
Description
Technical Field
[0001] The invention relates to the field of high-refractive polycarbonate resin and copolycarbonate resin, and in particular to a copolymerized polycarbonate resin, a preparation method and application thereof. Background Art
[0002] Polycarbonate has excellent mechanical properties, good dimensional stability, high heat resistance, low water absorption and high optical transparency, so it is widely used in the fields of electronics, aerospace, building materials, transparent packaging containers, optical films, optical lenses, etc. However, the refractive index of bisphenol A polycarbonate currently used in these fields is only 1.58, and it has high birefringence, making it difficult to use in the imaging and lens fields;
[0003] Patent CN102307930B discloses a copolycarbonate containing 9,9'-bis[4-(2-hydroxyethoxy)phenyl]fluorene (BPEF) and bis(4-hydroxyphenyl)sulfide (TDP). From its examples, it can be found that the introduction of TDP as an S-containing element has little effect on the refractive index, but as the TDP content increases, the BPEF content decreases, and the glass transition temperature of the copolycarbonate decreases; the introduction of sulfur can easily make the product yellowish, the glass transition temperature decreases, and the thermal stability decreases. Therefore, in some thermoplastic resins, the copolycarbonate material prepared by introducing sulfur elements to increase the refractive index is not the best choice for high-precision optical instruments;
[0004] Mitsubishi Gas Chemical Co., Ltd. disclosed in patent CN109476835B a copolycarbonate formed by combining 9,9'-bis[4-(2-hydroxyethoxy)phenyl]fluorene (BPEF), 9,9'-bis[3-phenyl-4-(2-hydroxyethoxy)phenyl]fluorene (BPPEF), 9,9'-bis[6-(2-hydroxyethoxy)naphthalene-2-yl]fluorene (BNEF) and 2,2'-bis(2-hydroxyethoxy)-1,1'-binaphthyl (BHEBN). It can be seen from the manufacturing examples of the patent that the contributions of the BNEF structural unit, BHEBN structural unit, BPPEF structural unit and BPEF structural unit in the copolymer to the refractive index decrease in sequence.
[0005] Patent CN112175178B discloses a series of polycarbonates or copolycarbonates prepared from dihydroxy compounds with high benzene ring content. Although the published refractive index can be as high as 1.7, the weight average molecular weight of the polycarbonate resin in the patent embodiment is less than 14,000. The low molecular weight makes these high-refractive polycarbonate resin materials brittle and difficult to process and shape, making them difficult to use.
[0006] Therefore, there is currently a lack of a polycarbonate resin that has a high refractive index, a high glass transition temperature and a high molecular weight to meet the application requirements for imaging lenses in high-precision optical instruments. Summary of the invention
[0007] In order to solve the above technical problems, the present invention provides a polycarbonate resin having a high refractive index, a high glass transition temperature and a high weight average molecular weight to meet the application requirements for imaging lenses in high-precision optical instruments.
[0008] The technical solution of the present invention is as follows:
[0009] A copolymer polycarbonate resin comprising a structural unit represented by general formula (III), a structural unit represented by general formula (II) and / or a structural unit represented by general formula (I);
[0010]
[0011] In the structural unit represented by the general formula (I), X represents a straight-chain alkyl group with 1 to 4 carbon atoms, R1 and R2 are independently selected from hydrogen atoms, alkyl groups with 1 to 3 carbon atoms, and aryl groups with 6 to 10 carbon atoms, and a and b are independently integers of 1 to 4;
[0012]
[0013] In the structural unit represented by the general formula (II), Y represents a straight-chain alkyl group having 1 to 4 carbon atoms, and c and d each independently represent an integer of 1 to 4;
[0014]
[0015] In the structural unit represented by the general formula (III), Z represents a straight-chain alkyl group having 1 to 4 carbon atoms, and e and f each independently represent an integer of 0 to 4;
[0016] Wherein, based on the total amount of the structural units as 100%, the proportion of the structural units represented by the general formula (I) is 0 to 90 mol%;
[0017] The proportion of the structural unit represented by the general formula (II) is 0 to 90 mol%;
[0018] The ratio of the structural unit represented by the general formula (III) is 10 to 100 mol%.
[0019] Preferably, taking the total amount of the structural units as 100%,
[0020] The proportion of the structural unit represented by the general formula (I) is 0 to 60 mol%;
[0021] The proportion of the structural unit represented by the general formula (II) is 0 to 60 mol%;
[0022] The ratio of the structural unit represented by the general formula (III) is 30 to 100 mol%.
[0023] Furthermore, taking the total amount of the structural unit as 100%,
[0024] The proportion of the structural unit represented by the general formula (I) is 0-50 mol%, for example, it can be 0 mol%, 20 mol%, 30 mol%, 40 mol%, 50 mol%, any value between 0 mol% and 50 mol%, or any interval between any two values.
[0025] The proportion of the structural unit represented by the general formula (II) is 0 to 50 mol%, for example, 0 mol%, 20 mol%, 30 mol%, 40 mol%, 50 mol%, any value between 0 mol% and 50 mol%, or any interval between any two values.
[0026] The proportion of the structural unit represented by the general formula (III) is 40 to 100 mol%; for example, it can be 40 mol%, 50 mol%, 60 mol%, 70 mol%, 80 mol%, 90 mol%, 100 mol%, and any value between 40 mol% and 100 mol% or any interval between any two values.
[0027] Preferably, at least one of R1 and R2 in the structural unit represented by the general formula (I) is selected from a hydrogen atom or an aromatic group having 6 to 10 carbon atoms.
[0028] Furthermore, in the structural unit represented by the general formula (I), R1 and R2 are both selected from hydrogen atoms or aromatic groups having 6 to 10 carbon atoms.
[0029] Preferably, in the structural unit represented by the general formula (I), R1 and R2 are both selected as aromatic groups having 6 to 10 carbon atoms.
[0030] According to the present invention, the aryl group having 6 to 10 carbon atoms refers to a phenyl group and / or a naphthyl group.
[0031] Preferably, in the structural unit represented by the general formula (I), R1 and R2 are both selected as naphthyl.
[0032] Preferably, the weight average molecular weight (Mw) of the polycarbonate resin is 20,000 to 100,000;
[0033] Furthermore, the weight average molecular weight (Mw) of the polycarbonate resin is preferably 25,000 to 80,000;
[0034] Furthermore, the weight average molecular weight (Mw) of the polycarbonate resin is preferably 35,000 to 70,000; for example, it may be 35,000, 40,000, 50,000, 60,000, 70,000, or any two values or any interval between any two values.
[0035] The refractive index (nD) of the polycarbonate resin is 1.660 to 1.930;
[0036] Furthermore, the refractive index (nD) of the polycarbonate resin is preferably 1.671 to 1.930;
[0037] Furthermore, the refractive index (nD) of the polycarbonate resin is preferably 1.681 to 1.930.
[0038] The glass transition temperature (Tg) of the polycarbonate resin is 145 to 210°C;
[0039] Further, the glass transition temperature (Tg) of the polycarbonate resin is preferably 150 to 210°C;
[0040] Furthermore, the glass transition temperature (Tg) of the polycarbonate resin is preferably 160-210°C.
[0041] The light transmittance of the polycarbonate resin in the present invention is 86%-89%, preferably 87%-88%.
[0042] According to the present invention, the linear alkyl group having 1 to 4 carbon atoms refers to at least one of a methyl group, an ethyl group, an n-propyl group, and an n-butyl group.
[0043] A method for preparing a copolymerized polycarbonate resin, comprising subjecting the dihydroxy compound comprising a structural unit represented by general formula (III), a structural unit represented by general formula (II) and / or a structural unit represented by general formula (I) as described above to a melt transesterification polycondensation process with a carbonic acid diester compound to obtain the copolymerized polycarbonate resin.
[0044] Furthermore, the aforementioned melt transesterification polycondensation step needs to be carried out under the action of a catalyst; examples of the catalyst include alkali metal compounds, alkaline earth metal compounds, nitrogen-containing compounds and transesterification catalysts.
[0045] Furthermore, the melt transesterification polycondensation process reaction comprises the following steps:
[0046] Step 1: Performing an ester exchange reaction under heating conditions, normal pressure or reduced pressure, while removing small molecular byproducts;
[0047] Step 2: Under heating and high vacuum, a polycondensation reaction is carried out, accompanied by further removal of small molecular by-products, to obtain a polycarbonate resin.
[0048] In step 1, the reaction is first carried out under heating conditions of 160 to 240° C., preferably 180 to 200° C.; the reaction time is 0.5 to 6 hours, preferably 2 to 4 hours;
[0049] In step 2, the degree of decompression is increased, and the temperature is raised to 210-220° C., the reaction is carried out for 0.5 hours, small molecule by-products are removed, and the temperature is then raised to 230-240° C., the decompression is reduced to less than 1 Torr, preferably 0.1-0.5 Torr, and the decompression time is 0.5-1 hour. Then, the reaction is continued under this condition for 0.5-2 hours. When the stirring reaches a predetermined value, the heating is stopped, and nitrogen is filled to restore the system to normal pressure and cool.
[0050] The specific steps of filling with nitrogen are as follows: after the reaction is completed, nitrogen is introduced to restore the pressure in the reaction bottle to normal pressure, the product is dissolved using a first solvent such as dichloromethane, and after dissolution, it is slowly poured into a beaker filled with a second solvent such as anhydrous ethanol, and stirred to precipitate the polycarbonate resin, washed with ethanol, and then vacuum dried.
[0051] In the present invention, the preferred catalyst is an alkali metal compound, and lithium acetylacetonate is more preferably used as the catalyst.
[0052] Furthermore, the carbonic acid diester compound is at least one selected from dimethyl carbonate, diphenyl carbonate, diethyl carbonate, dipropyl carbonate, dibutyl carbonate, ditolyl carbonate, bis(chlorophenyl) carbonate and dicyclohexyl carbonate.
[0053] Furthermore, the carbonic acid diester compound is preferably diphenyl carbonate.
[0054] In the present invention, the structural unit represented by the general formula (I) can be prepared from the following dihydroxy compounds: 2,2'-bis(1-hydroxymethoxy)-1,1'-binaphthyl, 2,2'-bis(2-hydroxyethoxy)-1,1'-binaphthyl, 2,2'-bis(3-hydroxypropoxy)-1,1'-binaphthyl, 2,2'-bis(4-hydroxybutoxy)-1,1'-binaphthyl, 2,2'-bis(2-hydroxyethoxy-3-methyl)-1,1'-binaphthyl,
[0055] 2,2'-bis(2-hydroxyethoxy-3-ethyl)-1,1'-binaphthyl, 2,2'-bis(2-hydroxyethoxy-3-n-propyl)-1,1'-binaphthyl,
[0056] 2,2'-bis(2-hydroxyethoxy-3-isopropyl)-1,1'-binaphthyl, 2,2'-bis(2-hydroxymethoxy-3-phenyl)-1,1'-binaphthyl,
[0057] 2,2'-bis(2-hydroxyethoxy-3-phenyl)-1,1'-binaphthyl, 2,2'-bis(2-hydroxymethoxy-3-naphthyl)-1,1'-binaphthyl,
[0058] 2,2'-bis(2-hydroxyethoxy-3-naphthyl)-1,1'-binaphthyl, etc., among which 2,2'-bis(2-hydroxyethoxy)-1,1'-binaphthyl, 2,2'-bis(2-hydroxyethoxy-3-phenyl)-1,1'-binaphthyl, and 2,2'-bis(2-hydroxyethoxy-3-naphthyl)-1,1'-binaphthyl are preferred, and 2,2'-bis(2-hydroxyethoxy-3-naphthyl)-1,1'-binaphthyl is more preferred;
[0059] In the present invention, the structural unit represented by the general formula (II) can be prepared from the following dihydroxy compounds: 9,9'-bis[6-(1-hydroxymethoxy)-naphthalene-2-yl]fluorene, 9,9'-bis[6-(2-hydroxyethoxy)-naphthalene-2-yl]fluorene, 9,9'-bis[6-(3-hydroxypropoxy)-naphthalene-2-yl]fluorene, 9,9'-bis[6-(4-hydroxybutoxy)-naphthalene-2-yl]fluorene, etc., among which 9,9'-bis[6-(2-hydroxyethoxy)-naphthalene-2-yl]fluorene is preferred;
[0060] In the present invention, the structural unit represented by the general formula (III) can be prepared from the following dihydroxy compounds: 1,8-naphthalenediol, 1,7-naphthalenediol, 1,6-naphthalenediol, 1,5-naphthalenediol, 2,6-naphthalenediol, 2,7-naphthalenediol, 1,8-bis(hydroxymethoxy)naphthalene, 1,7-bis(hydroxymethoxy)naphthalene, 2,6-bis(hydroxymethoxy)naphthalene, 1,6-bis(hydroxy-2-ethoxy)naphthalene, 2,6-bis(hydroxy-2-ethoxy)naphthalene, 1,5-bis(hydroxy-3-propoxy)naphthalene, 2,6-bis(hydroxy-4-butoxy)naphthalene, etc., among which 2,6-naphthalenediol is preferred.
[0061] In the present invention, the molar ratio of the catalyst to the carbonic acid diester compound can be selected in a wide range; preferably, the molar ratio of the catalyst to the carbonic acid diester compound is (0.01-0.1):100; preferably (0.01-0.05):100.
[0062] In the present invention, the molar ratio of the total amount of dihydroxy compounds used to prepare the structural unit represented by the general formula (III), the structural unit represented by the general formula (II) and / or the structural unit represented by the general formula (I) to the carbonic acid diester compound can be selected within a wide range. In a specific embodiment of the present invention, the molar ratio of the total amount of dihydroxy compounds used to prepare the structural unit represented by the general formula (III), the structural unit represented by the general formula (II) and / or the structural unit represented by the general formula (I) to the carbonic acid diester compound is (0.98-1.02):1, preferably (0.98-1):1, and more preferably 1:1.
[0063] A copolymer polycarbonate resin used in all optical lens fields including electronics, aerospace, building materials, transparent packaging containers and optical films.
[0064] Due to the adoption of the above technical solution, the beneficial effects of the present invention are as follows:
[0065] The present application provides a polycarbonate resin having a high refractive index, a high glass transition temperature and a high weight-average molecular weight, which is easier to process and shape, helps to reduce the thickness of the lens, and meets the application requirements for imaging lenses in high-precision optical instruments. DETAILED DESCRIPTION
[0066] The present invention is described in detail below in conjunction with specific embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the contents of the present invention still fall within the scope of protection of the present invention.
[0067] The performance evaluations in Examples 1 to 14 and Comparative Examples 1 to 6 were performed on samples prepared using the following method:
[0068] Step 1: Dissolve 5 g of the obtained polycarbonate resin in 40 ml of dichloromethane. After it is fully dissolved, apply it on a small film coating sample making machine. The film thickness of the sample making machine is set to 0.02 mm. At room temperature, after the solvent evaporates, remove the film sample and place it for 2 hours for optical performance testing.
[0069] Step 2: Use the injection molding method, the injection molding machine segment temperature is between 220-300°C, the mold temperature is 120-180°C, and the mold parameters are sheet thickness 1mm, length 2cm, and width 1cm.
[0070] The evaluation indexes in Examples 1 to 14 and Comparative Examples 1 to 6 were evaluated using the following method:
[0071] Indicator 1: Glass transition temperature (Tg)
[0072] The samples were subjected to DSC measurement using a TA DSC 2920 instrument in a nitrogen atmosphere (50 mL / min) at a temperature ramp rate of 10°C / min.
[0073] Index 2: Weight average molecular weight (Mw)
[0074] The weight average molecular weight (Mw) can be measured by a Waters 1515 pump and a 2414 refractive index detector with two columns (PLgel 5mm Mixed-C 300-7.5mm) at 35° C. Chloroform is used as the eluent at a flow rate of 1 mL / min and polystyrene standards are used for calibration.
[0075] Indicator 3: Refractive index (nD)
[0076] The refractive index of samples (a) and (b) was measured at a wavelength of 589 nm on an Abbe refractometer (WYA (2WAJ)) at room temperature.
[0077] Indicator 4: Abbe number (v)
[0078] According to the method in (3), the refractive indices nC, nD and nF at wavelengths of 486 nm, 589 nm and 656 nm were measured at room temperature, and the Abbe number was calculated using the formula v = (nD-1) / (nF-nC).
[0079] Indicator 5: Light transmittance
[0080] Transmittance / Haze Meter Conduct a test.
[0081] Embodiment 1:
[0082] The raw materials such as 0.05 mol of diphenyl carbonate (hereinafter referred to as "DPC"), 0.0315 mol of 2,6-naphthalenediol (hereinafter referred to as "DNT"), 0.0185 mol of 9,9'-bis[6-(2-hydroxyethoxy)naphthalene-2-yl]fluorene (hereinafter referred to as "BNEF") and 2.5×10 -5 mol, placed in a 100ml round-bottom flask with three mouths, N2 was passed to replace the air in the system, and heated in a N2 atmosphere, the temperature gradually increased from room temperature to 140-160°C, the reaction raw materials completely melted into a colorless transparent liquid, and then the temperature was continued to rise to 180°C, maintained for 2 hours, and then slowly reduced to 100Torr within 0.5 hours, the temperature was gradually increased to 220°C, and the reaction was continued for 0.5 hours. Finally, the temperature was raised to 240°C, the pressure was reduced to below 1Torr within 0.5 hours, and the reaction was continued for 0.5 hours.
[0083] After the reaction is completed, N2 is introduced to restore the reaction bottle to normal pressure. The product is dissolved with dichloromethane and slowly poured into a beaker filled with anhydrous ethanol and stirred to precipitate the product. After washing with ethanol, it is vacuum dried at 100°C for 8 hours. The sample is used for sample preparation and test characterization.
[0084] Embodiment 2:
[0085] 0.05 mol of DPC, 0.04 mol of DNT, 0.01 mol of BNEF and 2.5×10 -5 mol, placed in a 100 ml round-bottom flask with three necks, and the subsequent process was the same as in Example 1.
[0086] Embodiment 3:
[0087] 0.05 mol of DPC, 0.05 mol of DNT and 2.5×10 -5 mol, placed in a 100 ml round-bottom flask with three necks, and the subsequent process was the same as in Example 1.
[0088] Embodiment 4:
[0089] 0.05 mol of DPC, 0.0025 mol of 2,2'-bis(2-hydroxyethoxy-3-naphthyl)-1,1'-binaphthyl (hereinafter referred to as "BHENBN"), 0.015 mol of BNEF, 0.0325 mol of DNT and 2.5×10 - 5 mol, placed in a 100 ml round-bottom flask with three necks, and the subsequent process was the same as in Example 1.
[0090] Embodiment 5:
[0091] 0.05 mol of DPC, 0.0025 mol of BHENBN, 0.005 mol of BNEF, 0.0425 mol of DNT and 2.5×10 -5 mol, placed in a 100 ml round-bottom flask with three necks, and the subsequent process was the same as in Example 1.
[0092] Embodiment 6:
[0093] 0.05 mol of DPC, 0.0025 mol of BHENBN, 0.0475 mol of DNT and 2.5×10 -5 mol, placed in a 100 ml round-bottom flask with three necks, and the subsequent process was the same as in Example 1.
[0094] Embodiment 7:
[0095] 0.05 mol of DPC, 0.005 mol of BHENBN, 0.0125 mol of BNEF, 0.0325 mol of DNT and 2.5×10 -5 mol, placed in a 100 ml round-bottom flask with three necks, and the subsequent process was the same as in Example 1.
[0096] Embodiment 8:
[0097] 0.05 mol of DPC, 0.005 mol of BHENBN, 0.0075 mol of BNEF, 0.0375 mol of DNT and 2.5×10 -5 mol, placed in a 100 ml round-bottom flask with three necks, and the subsequent process was the same as in Example 1.
[0098] Embodiment 9:
[0099] 0.05 mol of DPC, 0.005 mol of BHENBN, 0.0025 mol of BNEF, 0.0425 mol of DNT and 2.5×10 -5 mol, placed in a 100 ml round-bottom flask with three necks, and the subsequent process was the same as in Example 1.
[0100] Embodiment 10:
[0101] 0.05 mol of DPC, 0.0075 mol of BHENBN, 0.01 mol of BNEF, 0.0325 mol of DNT and 2.5×10 -5 mol, placed in a 100 ml round-bottom flask with three necks, and the subsequent process was the same as in Example 1.
[0102] Embodiment 11:
[0103] 0.05 mol of DPC, 0.0075 mol of BHENBN, 0.005 mol of BNEF, 0.0375 mol of DNT and 2.5×10 -5 mol, placed in a 100 ml round-bottom flask with three necks, and the subsequent process was the same as in Example 1.
[0104] Embodiment 12:
[0105] 0.05 mol of DPC, 0.0075 mol of BHENBN, 0.0425 mol of DNT and 2.5×10 -5mol, placed in a 100 ml round-bottom flask with three necks, and the subsequent process was the same as in Example 1.
[0106] Embodiment 13:
[0107] 0.05 mol of DPC, 0.009 mol of BHENBN, 0.0085 mol of BNEF, 0.0325 mol of DNT and 2.5×10 -5 mol, placed in a 100 ml round-bottom flask with three necks, and the subsequent process was the same as in Example 1.
[0108] Embodiment 14:
[0109] 0.05 mol of DPC, 0.009 mol of BHENBN, 0.001 mol of BNEF, 0.04 mol of DNT and 2.5×10 -5 mol, placed in a 100 ml round-bottom flask with three necks, and the subsequent process was the same as in Example 1.
[0110] Comparative Example:
[0111] Comparative Example 1:
[0112] 0.05 mol of DPC, 0.025 mol of 2,2'-bis[2-hydroxyethoxy-3-phenyl]-1,1'-binaphthyl (hereinafter referred to as "BHEPBN"), 0.0125 mol of BNEF, 0.0125 mol of DNT and other raw materials and 2.5×10 -5 mol, placed in a 100ml round-bottom flask with three mouths, N2 was passed to replace the air in the system, and heated in a N2 atmosphere, the temperature gradually increased from room temperature to 140-160°C, the reaction raw materials completely melted into a colorless transparent liquid, and then the temperature was continued to rise to 180°C, maintained for 2 hours, and then slowly reduced to 100Torr within 0.5 hours, the temperature was gradually increased to 220°C, and the reaction was continued for 0.5 hours. Finally, the temperature was raised to 240°C, the pressure was reduced to below 1Torr within 0.5 hours, and the reaction was continued for 0.5 hours.
[0113] After the reaction is completed, N2 is introduced to restore the reaction bottle to normal pressure. The product is dissolved with dichloromethane and slowly poured into a beaker filled with anhydrous ethanol and stirred to precipitate the product. After washing with ethanol, it is vacuum dried at 100°C for 8 hours. The sample is used for sample preparation and test characterization.
[0114] Comparative Example 2:
[0115] 0.05 mol of DPC, 0.01 mol of BHEPBN, 0.0175 mol of BNEF, 0.0225 mol of DNT and 2.5×10 -5 mol, placed in a 100ml round-bottom flask with three necks, N2 was passed to replace the air in the system, and heated under N2 atmosphere, the temperature gradually increased from room temperature to the range of 140-160°C, the reaction raw materials were completely melted into a colorless transparent liquid, and the subsequent process was the same as Comparative Example 1.
[0116] Comparative Example 3:
[0117] 0.05 mol of DPC, 0.025 mol of 2,2'-bis(2-hydroxyethoxy)-1,1'-binaphthyl (hereinafter referred to as "BHEBN"), 0.0125 mol of BNEF, 0.0125 mol of DNT and other raw materials and 2.5×10 -5 mol, placed in a 100ml round-bottom flask with three necks, N2 was passed to replace the air in the system, and heated under N2 atmosphere, the temperature gradually increased from room temperature to the range of 140-160°C, the reaction raw materials were completely melted into a colorless transparent liquid, and the subsequent process was the same as Comparative Example 1.
[0118] Comparative Example 4:
[0119] 0.05 mol of DPC, 0.01 mol of 2,2'-bis(2-hydroxyethoxy)-1,1'-binaphthyl (hereinafter referred to as "BHEBN"), 0.0175 mol of BNEF, 0.0225 mol of DNT and other raw materials and 2.5×10 -5 mol, placed in a 100ml round-bottom flask with three necks, N2 was passed to replace the air in the system, and heated under N2 atmosphere, the temperature gradually increased from room temperature to the range of 140-160°C, the reaction raw materials were completely melted into a colorless transparent liquid, and the subsequent process was the same as Comparative Example 1.
[0120] Comparative Example 5:
[0121] 0.05 mol of DPC, 0.035 mol of BHENBN, 0.015 mol of DNT and 2.5×10 -5 mol, placed in a 100ml round-bottom flask with three necks, N2 was passed to replace the air in the system, and heated under N2 atmosphere, the temperature gradually increased from room temperature to the range of 140-160°C, the reaction raw materials were completely melted into a colorless transparent liquid, and the subsequent process was the same as Comparative Example 1.
[0122] Comparative Example 6:
[0123] 0.05 mol of DPC, 0.025 mol of BHENBN, 0.025 mol of DNT and 2.5×10 -5 mol, placed in a 100ml round-bottom flask with three necks, N2 was passed to replace the air in the system, and heated under N2 atmosphere, the temperature gradually increased from room temperature to the range of 140-160°C, the reaction raw materials were completely melted into a colorless transparent liquid, and the subsequent process was the same as Comparative Example 1.
[0124] The experimental results of the above embodiments and comparative examples are listed in Tables 1 and 2.
[0125] Table 1: Comparison of various indicators of Examples 1 to 14 and Comparative Examples 1 to 6
[0126]
[0127]
[0128] It can be seen from the above table:
[0129] In terms of contribution to the refractive index, DNT>BNEF>BHENBN>BHEPBN>BHEBN, which is determined by the benzene ring content and group structure in the monomer;
[0130] For BHENBN, BHEPBN and BHEBN, their main structures are similar, and the difference lies in the substituents. Adding benzene rings to the substituents will increase the contribution to the refractive index;
[0131] Although BNEF has slightly fewer benzene rings than BHENBN, its special cardo structure also makes a greater contribution to the refractive index;
[0132] The greater contribution of DNT is due to the fact that in its structure, except for the benzene ring / or naphthalene ring and the functional group hydroxyl group, there are no other group structures (such as methylene), so the benzene ring content in the molecule accounts for a higher percentage. Methylene has a lowering effect on the refractive index, so DNT has a higher refractive index;
[0133] As for the contribution to the glass transition temperature, the rule is consistent with that of the refractive index contribution. This is because the benzene ring has a rigid structure, which can increase the refractive index and the glass transition temperature at the same time. The methylene group has a flexible structure, which can reduce the refractive index and the glass transition temperature at the same time. The weight-average molecular weight increases because in the ester exchange reaction system, the phenolic hydroxyl group has a higher reactivity than the alcoholic hydroxyl group, which is beneficial to the molecular chain growth reaction of polycarbonate.
[0134] By adjusting the ratio of the monomers BHENBN, BNEF and DNT and copolymerizing them with DPC, a copolycarbonate resin with a refractive index of up to 1.920 and a glass transition temperature of 207.87°C can be obtained.
[0135] Table 2: Comparison of rigidity indexes of Examples 1 to 14
[0136]
[0137] By adjusting the proportions of DNT, BNEF and BHENBN, a copolycarbonate resin with a weight-average molecular weight, glass transition temperature and refractive index at an optimal level and rigidity meeting the standards is obtained.
[0138] It should be noted that the above-described embodiments are only partial experimental data and are only used to explain the present invention and do not constitute any limitation of the present invention. All publications, patent applications, patents and other references mentioned in this specification are all incorporated herein by reference. Unless otherwise defined, all technical and scientific terms used in this specification have the meanings conventionally understood by those skilled in the art. In the event of conflict, the definition of this specification shall prevail.
Claims
1. A copolymer polycarbonate resin, characterized in that: The carbonate resin is composed of repeated structural units represented by general formula (III), structural units represented by general formula (II) and / or structural units represented by general formula (I); ; In the structural unit represented by the general formula (I), X represents a straight-chain alkyl group with 1 to 4 carbon atoms, R1 and R2 are independently selected from a hydrogen atom, an alkyl group with 1 to 3 carbon atoms, and an aryl group with 6 to 10 carbon atoms, and a and b are independently integers of 1 to 4; ; In the structural unit represented by the general formula (II), Y represents a straight-chain alkyl group having 1 to 4 carbon atoms, and c and d each independently represent an integer of 1 to 4; ; In the structural unit represented by the general formula (III), Z represents a straight-chain alkyl group having 1 to 4 carbon atoms; Wherein, based on the total amount of the structural units as 100%, the proportion of the structural units represented by the general formula (I) is 0-90 mol%; The proportion of the structural unit represented by the general formula (II) is 0-90 mol%; The proportion of the structural unit represented by the general formula (III) is 10-75 mol%; In the structural unit represented by the general formula (III), the values of e and f are 0, one of the substituents is located at the 2-position of the naphthalene ring, and the other substituent is located at the 6-position of the naphthalene ring.
2. A copolymerized polycarbonate resin according to claim 1, characterized in that: Taking the total amount of structural units as 100%, The proportion of the structural unit represented by the general formula (I) is 0-60 mol%; The proportion of the structural unit represented by the general formula (II) is 0-60 mol%; The proportion of the structural unit represented by the general formula (III) is 30-75 mol %.
3. A copolymerized polycarbonate resin according to claim 1, characterized in that: In the structural unit represented by the general formula (I), at least one of R1 and R2 is selected from a hydrogen atom or an aromatic group having 6 to 10 carbon atoms.
4. A copolymerized polycarbonate resin according to claim 1, characterized in that: In the structural unit represented by the general formula (I), R1 and R2 are both selected as aromatic groups having 6 to 10 carbon atoms.
5. A copolymerized polycarbonate resin according to claim 1, characterized in that: In the structural unit represented by the general formula (I), R1 and R2 are both selected as naphthyl.
6. A copolymer polycarbonate resin according to any one of claims 1 to 5, characterized in that: The weight average molecular weight (Mw) of the polycarbonate resin is 20,000 to 100,000; The refractive index (nD) of the polycarbonate resin is 1.660-1.930; The glass transition temperature (Tg) of the polycarbonate resin is 145-210°C.
7. A method for preparing a copolymerized polycarbonate resin, characterized in that: The copolymerized polycarbonate resin according to any one of claims 1 to 6 is obtained by subjecting a dihydroxy compound and a carbonic acid diester compound to a melt transesterification polycondensation process.
8. An application of a copolymerized polycarbonate resin, characterized in that: The copolymer polycarbonate resin described in any one of claims 1 to 6 is used in the field of optical lenses including electronic appliances, aerospace, building materials, transparent packaging containers and optical films.
Citation Information
Patent Citations
Copolycarbonate and optical lens
CN102307930B
Polycarbonate resin, its manufacturing method and optical lens
CN109476835B
A polycarbonate, its preparation method and application
CN112175178B
Copolycarbonate with high refractive index, high heat resistance and high weather resistance as well as preparation method and application thereof
CN113956458A
polycarbonate copolymer
JP1993310903A